Keefektifan Pijat Bayi dengan Pengenceran Minyak Esensial Bawang Putih Bima (Allium Sativum) dalam Mengurangi Gejala Kolik pada Bayi - Susanti Susanti; Erni Faturahmah; Sumarni Sumarni; Ade Sucipto; Zahratul Hayati (Faletehan Health Journal, 2026)
Infantile colic is one of the common health problems experienced by infants in early life, characterized by excessive crying and difficulty being soothed. Garlic (Allium Sativum) is known to contain bioactive compounds that potentially provide antispasmodic,carminative, and anti-inflammatory effects. Aim of this study was to examine the effectiveness of baby massage with Bima garlic (Allium Sativum) essential oil dilution in reducing infantile colic symptoms in babies. This study employed a quasi-experimental design with a pre-test–post-test control group design. The sample consisted of 50 infants divided into two groups: experimental group (n =25) that received baby massage with Bima garlic essential oil dilution and control group (n= 25) that received baby massage without oil. The results showed a significant reduction in colic symptoms in both groups after the intervention. However, the decrease was greater in the experimental group. Statistical analysis indicated a significant difference in post-test scores between the experimental and the control group (p < 0.001). This intervention may be considered an evidence-based, locally grounded complementary therapy that is safe, affordable, and easy to implement in pediatric nursing practice.